Integrated Corporate Social Responsibility and Social Enterprise Synergy: A Multi-theoretic Perspective and Future Agenda - Kour, Palvinder; Saurabh; Bukhari, Syeda Shazia (Journal of Knowledge Management Practice, 2026)
Despite the fact that CSR and SEs pursue complementary objectives, their synergistic relationships have not been thoroughly examined. SEs are driven by their mission to generate enduring social value, whereas CSR initiatives are shaped by the pressures of institutional and stakeholder legitimacy. This study integrates theories of stakeholder, institutional legitimacy, and resource dependence to create a framework that elucidates the drivers and outcomes of CSR–SE partnerships. These collaborations not only improve the reputation, trust, and resources of SEs but also promote sustainability and facilitate cross-industry learning, thus contributing to the advancement of theory and practice in cross-sector cooperation.